Answer:
Following are the solution to the given point:
Step-by-step explanation:
Please find the comp[lete question in the attached file.
Given:
[tex]\bold{ \lim_{n \to \ \infty} (1+ \frac{r}{n})^{nt} =e^{rt}}[/tex]
In point 1:
[tex]\to y = (1+ \frac{r}{n})^{nt}[/tex]
In point 2:
[tex]\to \ln (y)= nt \ln(1+ \frac{r}{n})[/tex]
In point 3:
Its key thing to understand, which would be that you consider the limit n to[tex]\infty[/tex], in which r and t were constants!
[tex]=lim_{n \to \ \infty} \ln (y) = lim_{n \to \ \infty} nt \ln(1+\frac{r}{n})\\\\= lim_{n \to \ \infty} \frac{\ln(1+\frac{r}{n})}{\frac{1}{nt}}\\\\= lim_{n \to \ \infty} \frac{\frac{-r}{\frac{n^2}{(1+\frac{r}{n})}}}{- \frac{1}{n^2t}}\\\\= lim_{n \to \ \infty} \frac{\frac{rn^2t}{n^2}}{(1+\frac{r}{n})}\\\\= lim_{n \to \ \infty} \frac{rt}{(1+\frac{r}{n})}\\\\= \frac{rt}{(1+\frac{r}{0})}\\\\=rt[/tex]
In point 4:
[tex]\to \lim_{n \to \ \infty} = (1+\frac{r}{n})^{nt}[/tex] and
[tex]\to \lim_{n \to \ \infty} = A_0e^{rt}[/tex]